Baseline Blood Pressure Effect on the Benefit and Safety of Intra-Arterial Treatment in MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment of Acute Ischemic Stroke in the Netherlands). Issue 7 (July 2017) - Mulder, Maxim J.H.L.; Ergezen, Saliha; Lingsma, Hester F.; Berkhemer, Olvert A.; Fransen, Puck S.S.; Beumer, Debbie; van den Berg, Lucie A.; Lycklama à Nijeholt, Geert; Emmer, Bart J.; van der Worp, H. Bart; Nederkoorn, Paul J.; Roos, Yvo B.W.E.M.; et al.
Abstract : Background and Purpose—: High blood pressure (BP) is associated with poor outcome and the occurrence of symptomatic intracranial hemorrhage in acute ischemic stroke. Whether BP influences the benefit or safety of intra-arterial treatment (IAT) is not known. We aimed to assess the relation of BP with functional outcome, occurrence of symptomatic intracranial hemorrhage and effect of IAT. Methods—: This is a post hoc analysis of the MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment of Acute Ischemic Stroke in the Netherlands). BP was measured at baseline, before IAT or stroke unit admission. We estimated the association of baseline BP with the score on the modified Rankin Scale at 90 days and safety parameters with ordinal and logistic regression analysis. Effect of BP on the effect of IAT was tested with multiplicative interaction terms. Results—: Systolic BP (SBP) had the best correlation with functional outcome. This correlation was U-shaped; both low and high baseline SBP were associated with poor functional outcome. Higher SBP was associated with symptomatic intracranial hemorrhage (adjusted odds ratio, 1.25 for every 10 mm Hg higher SBP [95% confidence interval, 1.09–1.44]). Between SBP and IAT, there was no interaction for functional outcome, symptomatic intracranial hemorrhage, or other safety parameters; the absolute benefit of IAT was evident for the whole SBP range. The same was found for diastolic BP. Conclusions—: BP does not affect the benefit or safety of IAT in patients with acute ischemic stroke caused by proximal intracranial vessel occlusion. Our data provide no arguments to withhold or delay IAT based on BP. Clinical Trial Registration—: URL:http://www.isrctn.com . Unique identifier: ISRCTN10888758. Abstract : Supplemental Digital Content is available in the text.